Magnetic Field Measurements From Rome During the August–September 1859 Storms. Issue 6 (21st June 2020) - Blake, Seán P.; Pulkkinen, Antti; Schuck, Peter W.; Nevanlinna, Heikki; Reale, Oreste; Veenadhari, Bhaskara; Mukherjee, Shyamoli
Abstract: The geomagnetic storm (or "Carrington event") of 1–2 September 1859 is one of the largest geomagnetic disturbances on record. At the time, it caused widespread disruption to telegraph systems and was accompanied by aurorae seen overhead as far south as ∼29° magnetic latitude. The magnitude of the Carrington event means it remains a popular subject of study in the field of space weather, despite the sparse magnetic measurements available from the time. One set of measurements that is available is from the Rome observatory ("Collegio Romano, " magnetic latitude ∼38.6°). Here we transcribe these horizontal magnetic field data and convert them to nanoteslas. We find that the device used at Rome had an operational range of around 305 nT. Despite going off‐scale during the storm, the magnetometer at Rome recorded changes of hundreds of nanoteslas per minute and tens of nanoteslas per second in the horizontal magnetic field. Apart from the tabulated data, we also examine the reported off‐scale deviation of 3, 000 nT at Rome during the storm. While we could not explicitly locate this reported deviation in the tabulated data, we find that this deviation is comparable to magnetic variations seen at auroral latitudes for modern large magnetic storms, indicating that Rome was in the auroral oval during the morning of 2 September 1859. By comparing this large off‐scale deviation to modern geomagnetic data, we estimate that Rome may have experienced a maximum change of 420 nT min −1 . Key Points: The horizontal magnetic data recorded at Rome during the August–September 1859 storms is tabulated and converted to nanoteslas The reported horizontal deviation of ∼3, 000 nT is examined and found to be consistent with an expanded auroral oval Maximum changes of around 420 nT min −1 are estimated for Rome during the morning of 2 September 1859